Financial Literacy and Retirement Planning Trends: An Empirical investigation of Financial Planning in Saharsa District in Bihar - Mukesh Kumar Mishra (ResearchGate, 2025)
The study evaluates the current status of financial literacy and retirement planning trends in Saharsa district in Bihar through an empirical study. This study aims to examine the relationship between retirement benefits and saving behaviour after analysed a sample of 384 respondents to design a model that examines the relationship between retirement planning and financial literacy trends. The study reveals that behavioural, socio-economic, and financial factors significantly influence investment decisions, with financial literacy and risk also positively impacting these decisions. Financial literacy in India emerged in the 21st century, aiming to improve capital formation through saving and investment among rural households through a well-planned and promoted approach. The knowledge and abilities needed to manage financial resources in developing sectors are referred to as financial literacy. It improves abilities for more effective financial management and development economics policymaking. In welfare economics, this study investigates the connection between literacy and inclusion. The study in Saharsa district in Bihar reveals a significant lack of financial literacy and inclusion among the population, with varied attitudes and behaviours. Findings indicate that Respondents have low awareness of Retirement and Estate Planning, and feel their personal financial plans are imbalanced, requiring expert management and PMJDY is an important instrument for assessing financial literacy in India since it enhances Saharsa district's socioeconomic inclusion.
Keywords: D12; D14; D63; 330; Financial Psychology; Economics and Development; Banking; Financial Literacy